1996
DOI: 10.2151/jmsj1965.74.1_115
|View full text |Cite
|
Sign up to set email alerts
|

Super-and Sub-Harmonic Responses of Tropical Kelvin Waves to the Heating with a Seasonal Modulation

Abstract: By applying a seasonally modulated condensation heating on tropical Kelvin waves with a certain form of damping, the parametric instability and super (sub) harmonic response of the Kelvin waves are investigated. It is suggested that the excitation of intraseasonal oscillation and tropospheric QBO may be related to the superharmonic and subharmonic resonances with the seasonal cycle, respectively. The main features of the spatial structures and propagation of these resonant modes were shown and compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The result of this study is compared with the conclusion derived by Zhao and Takahashi (1996) who have proposed conversely that the intraseasonal and interannual oscillations may be excitation as the result of the superharmonic and subharmonic resonances with the seasonal cycle, respectively. They considered the response of the tropical Kelvin waves to the cumulus heating with a seasonal cycle under a certain form of damping to derive so-called Mathieu equation in a form:…”
Section: Results For a Run With An Annual Cyclementioning
confidence: 65%
See 1 more Smart Citation
“…The result of this study is compared with the conclusion derived by Zhao and Takahashi (1996) who have proposed conversely that the intraseasonal and interannual oscillations may be excitation as the result of the superharmonic and subharmonic resonances with the seasonal cycle, respectively. They considered the response of the tropical Kelvin waves to the cumulus heating with a seasonal cycle under a certain form of damping to derive so-called Mathieu equation in a form:…”
Section: Results For a Run With An Annual Cyclementioning
confidence: 65%
“…James and James (1989) reported that the interannual variability with periods of up to 10-40 years was generated internally by the non-linear dynamics of a simple primitive equation model with an imposed annual-cycle forcing. According to the recent study by Zhao and Takahashi (1996) forcing. It is our aim to investigate the parametric instability under a fully non-linear primitive equation model.…”
Section: Introductionmentioning
confidence: 99%